e-Government Initiatives of Four Philippine Cities - Gabrielle Iglesias (Philippine Institute for Development Studies (PIDS), 2010)
This study intends to provide a snapshot of the city government (in a developing country) as it uses information and communication technology (ICT) to transform its public service delivery and promote good urban governance. The volume of work related to services provided by local governments could be made more efficient, effective, transparent, accountable, and equitable using relevant technologies. In the Philippines, a Government Information Systems Plan (GISP) was approved and adopted as framework for all computerization efforts of key services and operations. This study used as case study samples four city governments (Caloocan, Muntinlupa, Antipolo, and Tagaytay) known to actively use ICT applications to determine: (1) the level of use of ICT, and (2) how their computerization efforts facilitate good urban governance. The e-governance framework used for this study has a phased ICT utilization wherein a government agency must first use ICT to improve its internal operations (e-administration), then its public service delivery (e-government), before finally being able to use ICT to improve its relationship with its constituents (e-governance).
Keywords: 330; information and communications technology (ICT); Philippines; local governance; e-government; e-administration; Kommunalverwaltung; Informationstechnik; E-Government; Philippinen